Indole Derivatives from the Egg Masses of Muricid Molluscs - Andrew R. Davis (Molecules, 2001)
A range of brominated indole derivatives were found in the egg masses of six species of muricid molluscs. Several non-brominated indoles were also present in the eggs of two Mediterranean Muricidae, although these were not found in the Australian species. Tyrindoleninone (3), was the only compound found in all six species and is likely to be responsible for the observed antimicrobial activity of these muricid egg masses [1,2]. These bioactive indoles appear to be characteristic of muricid egg masses and were not found in the egg masses from 17 species in different families of marine molluscs.